Climate change and the variability in the risk of single and compound climate extremes - Tavakol, Ameneh (Kansas State University, 2020)
Extreme weather and climate events have significantly influenced society and the environment. As the world has warmed, the warmer temperatures have triggered the frequency, severity, and duration of other extremes. In this study, the spatial and temporal patterns of heatwave frequency and duration were analyzed in the Mississippi River Basin (MRB) using the validated reanalysis (NCEP-NCAR) data for 1948‒2018. The heatwave was defined as at least two consecutive days when maximum temperature was higher than the 90th percentile. Over the 70-year period of study, the highest frequency of heatwaves was recorded in the west and north-west of the MRB with no significant increase over time. The results of the study confirmed the “warming hole” in the eastern-central United States with a significant decrease in the frequency of heatwaves. The longest heatwaves were found in southern and central MRB. Applying change-point analysis, an abrupt increase was found in the MRB in the percentage of area with heatwaves longer than 10 consecutive days since 1966. Impacts of heatwaves increase when multiple hazards occur simultaneously (e.g. heatwaves and high humidity) and lead to a compound extreme outcome. Heat-index was used to analyze the variability of compound high temperature and high humidity over time and space. Extreme daytime and nighttime hot-humid conditions were defined using the National Weather Services fixed thresholds. Spatially, southern MRB showed a higher frequency of extreme hot-humid events during both days and nights. There were no extreme nighttime hot-humid events in the east, west, and north-west MRB. Trend analysis discovered 16% and 8% significant upward trends in the daytime and nighttime extreme hot-humid events, respectively. In addition to single and bivariate extremes of the heatwave and hot-humid events, the trivariate extreme of hot, dry, and windy events (HDWs) was studied. Copula families, with the flexibility of modeling joint behavior of more than one variable, were applied to discover the probability of compound HDWs in the central United States. The empirical method (i.e., counting the frequency of events) was used to test the accuracy of the copula. Results discovered south-west Kansas and North Texas as hotspots, where most of the HDWs are expected. A combination of drought and heatwave, in 1980 and 2011, showed an accelerating influence on the frequency of HDWs. The dependence structure between variables (temperature, relative humidity, and wind) showed no influence on the compound HDWs in the warm season (May through September). Results suggested an increase in the risk of HDWs despite the wind speed drop in a majority of the central United States. The results of this study are useful for a better understanding of the nature and variability of single and compound extreme events in the central United States that would influence water resources, irrigation, crops, wildfire, and human, plant, and livestock health. Findings suggest a need for more effective risk management in discovered hotspots considering a changing climate.
Keywords: Climate extreme events; Compound extreme events; Copula; NCEP-NCAR; Hot, dry, and windy events; Heatwave and humid heatwave